2020
DOI: 10.1186/s12889-020-08940-x
|View full text |Cite
|
Sign up to set email alerts
|

Full vaccination coverage among children aged 12–23 months in Ethiopia: a systematic review and meta-analysis

Abstract: Background: Vaccination is one of the most cost-effective means of public health interventions to prevent childhood deaths from infectious diseases. Although several fragmented studies have been conducted concerning full vaccination coverage among children aged 12-23 months in Ethiopia, the pooled estimate has not been determined so far. Therefore, this systematic review and meta-analysis aims to estimate the pooled prevalence of full vaccination coverage among children aged 12-23 months in Ethiopian. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
(46 reference statements)
3
19
0
Order By: Relevance
“…Urban children had a 3.102 times greater chance of being fully vaccinated than rural children. The finding was consistent with studies done at a national level in Ethiopia, Somalia region, Jigijiga, Mecha, and Lay Armachiho, 5 , 14 , 17 , 18 , 37 but in contrast to studies done in Pawi and Tehuledere. 23 , 28 The disparities may be due to differences in modern health service utilization between urban and rural residents, with urban residents using modern health services more than rural residents.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Urban children had a 3.102 times greater chance of being fully vaccinated than rural children. The finding was consistent with studies done at a national level in Ethiopia, Somalia region, Jigijiga, Mecha, and Lay Armachiho, 5 , 14 , 17 , 18 , 37 but in contrast to studies done in Pawi and Tehuledere. 23 , 28 The disparities may be due to differences in modern health service utilization between urban and rural residents, with urban residents using modern health services more than rural residents.…”
Section: Discussionsupporting
confidence: 90%
“…The finding was consistent with studies done in SSA, Zimbabwe, the national level of Ethiopia, the Somalia region, and Sinana. 14 , 15 , 37 , 41 , 43 This could be attributed to differences in childcare practices, improved health-seeking behavior, and improved health-care access.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The country's frequent measles outbreaks and high child morbidity and mortality rates may be attributed to low immunization coverage. Around 40% of Ethiopian children do not benefit from immunization [ 18 ] and similar evidence showed that 26.8% of children were at risk of acquiring vaccine-preventable diseases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Forgetfulness and being unaware of the need to return for subsequent doses were among the common reasons for nonattendance to vaccination schedules, which are remediable through appropriate reminder services [ 28 , 37 , 38 , 40 , 42 - 47 ]. Studies have shown that achieving universal coverage with all recommended vaccines requires tailored strategies that address barriers to vaccination [ 15 , 16 , 28 , 48 - 50 ]. Thus, innovative strategies are required to reach the last mile where mobile technology can be effectively utilized to augment the immunization program.…”
Section: Introductionmentioning
confidence: 99%